Thermal conductivity of an organic phase change material/expanded graphite composite across the phase change temperature range and a novel thermal conductivity model. (15th September 2015) - Ling, Ziye; Chen, Jiajie; Xu, Tao; Fang, Xiaoming; Gao, Xuenong; Zhang, Zhengguo
Highlights: Expanded graphite can improve thermal conductivity of RT44HC by 20–60 times. Thermal conductivity of PCM/EG composites keeps constant before/after melting. Thermal conductivity of PCMs nearly doubled during phase changing. Thermal conductivity of composite PCM increases with density and percentage of EG. The simple model predicts thermal conductivity of EG-based composites accurately. Abstract: This work studies factors that affect the thermal conductivity of an organic phase change material (PCM), RT44HC/expanded graphite (EG) composite, which include: EG mass fraction, composite PCM density and temperature. The increase of EG mass fraction and bulk density will both enhance thermal conductivity of composite PCMs, by up to 60 times. Thermal conductivity of RT44HC/EG composites remains independent on temperature outside the phase change range (40–45 °C), but nearly doubles during the phase change. The narrow temperature change during the phase change allows the maximum heat flux or minimum temperature for heat source if attaching PCMs to a first (constant temperature) or second (constant heat flux) thermal boundary. At last, a simple thermal conductivity model for EG-based composites is put forward, based on only two parameters: mass fraction of EG and bulk density of the composite. This model is validated with experiment data presented in this paper and in literature, showing this model has general applicability to any composite of EG and poor thermal conductive materials.